Response to Instruction in Preschool: Results of Two Randomized Studies with Children At Significant Risk of Reading Difficulties - Lonigan, Christopher J. (J Educ Psychol, 2015)
Although response-to-instruction (RTI) approaches have received increased attention, few studies have evaluated the potential impacts of RTI approaches with preschool populations. This manuscript presents results of two studies examining impacts of Tier II instruction with preschool children. Participating children were identified as substantially delayed in the acquisition of early literacy skills despite exposure to high-quality, evidence-based classroom instruction. Study 1 included 93 children (M age = 58.2 months; SD = 3.62) attending 12 Title I preschools. Study 2 included 184 children (M age = 58.2 months; SD = 3.38) attending 19 Title I preschools. The majority of children were Black/African American, and about 60% were male. In both studies, eligible children were randomized to receive either 11 weeks of need-aligned, small-group instruction or just Tier I. Tier II instruction in Study 1 included variations of activities for code- and language-focused domains with prior evidence of efficacy in non-RTI contexts. Tier II instruction in Study 2 included instructional activities narrower in scope, more intensive, and delivered to smaller groups of children. Impacts of Tier II instruction in Study 1 were minimal; however, there were significant and moderate-to-large impacts in Study 2. These results identify effective Tier II instruction but indicate that the context in which children are identified may alter the nature of Tier II instruction that is required. Children identified as eligible for Tier II in an RTI framework likely require more intensive and more narrowly focused instruction than do children at general risk of later academic difficulties.